Current medical diagnosis & treatment 2015 - Papadakis, Maxine A.; McPhee, Stephen J.; Rabow, Michael W. (New York : McGraw-Hill Education/Medical, 2015)
Provides information on the signs, symptoms, epidemiology, etiology, and treatment of more than one thousand diseases and disorders; and includes drug treatment tables, color plates, NAEPP asthma guidelines, and other resources.
Includes bibliographical references and index